Hematopoietic recovery in repeatedly irradiated mice can be enhanced by a repeatedly administered combination of diclofenac and glucan - Hofer, M; Pospísil, M; Viklická, S; Vacek, A; Pipalová, I; Bartonícková, A (Journal of leukocyte biology, 1993)
A combination of diclofenac and glucan administered repeatedly in a protective regimen in the course of repeated gamma irradiation of mice (6 x 2 Gy during 3 weeks) enhanced granulopoiesis and other indices of hematopoietic recovery investigated from 3 to 7 days after the last radiation exposure. Repeated administration of diclofenac or glucan alone or treatment of the mice with the diclofenac-glucan combination given once before the first or the last radiation exposure did not induce such effects. The protective effect of the repeatedly administered combination of the drugs was realized despite the fact that the response of the serum colony-stimulating activity to the repeated combined drug administration was decreased at the end of the treatment regimen compared to that of mice given this drug combination only once. The combined treatment is supposed to act via increased proliferation of the hematopoietic stem or progenitor cells. Additivity or even synergism of the hematostimulatory action of glucan and of the strengthening of positive control of cell proliferation achieved by removing negatively acting prostaglandins (diclofenac action) may account for the radioprotective effects observed.
Keywords: Drug Interactions; diklofenak; Time Factors; hematopoéza; glukany; mužské pohlaví; Granulocytes; Glucans; Mice; záření gama; Mice, Inbred Strains; kostní dřeň; inbrední kmeny myší; granulocyty; buňky kostní dřeně; Macrophages; zvířata; Bone Marrow Cells; časové faktory; analýza kolonii tvořících jednotek; myši; makrofágy; Diclofenac; lékové interakce; hematopoetické kmenové buňky; Colony-Forming Units Assay; Hematopoiesis; Bone Marrow; Hematopoietic Stem Cells; Gamma Rays; Male; Animals